DISTRICT BANK OF NIŠ 1907‒1947 (Heritage, 2022)
During the Customs War of the Kingdom of Serbia and Austro-Hungary, a large number od discount banks were established in Serbia. One of them was the District Bank in Niš. In accordance with the business policy of Serbian banks in thet period, this bank also had its own companies, an automatic mill and a brick faktory.The Great War interrupted the work of banks in Serbia, and their property became the subject of exploitation by the occupiers. After the ene of the war, the District Bank renewed its work, and the most profitable part of the company was the mill. The brickyard worked poorly because the citizens did not have the funds to build new houses.In the period from 1921 to 1929, the District Bank operated successfully and regularly paid dividends to its shareholders. With the outbreak of the ecomomic crisis and falling prices for agricultural products, the District Bank found itsel in trouble because it had to srop working in its inustrial companies, and the withdrawal of funds from savings deposits left the bank without working capital. The bank was forced to seek protection and used it until 1942.It was one of the few banks that operated during the WWII and even incrased its capital. The change of the social system and the creation of socioalist Yugoslavia marked the end of the business of this financial institution.
Keywords: District bank of Niš, automatic mill, brick faktory, ecconomic crises, savings deposits, protection, liquidation